A hafnium tantalum oxide-single-walled carbon nanotube composite film and its preparation method and application
By using hafnium tantalum oxide-single-walled carbon nanotube composite film as the electrode material of supercapacitors, the problems of poor conductivity and limited specific capacitance of the existing electrode materials are solved, and electrode materials with high specific capacitance and good cycle performance are achieved.
Patent Information
- Application Number
- CN202310373377.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-07
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-04-07
AI Technical Summary
The existing supercapacitor electrode materials have problems such as poor conductivity, limited specific capacitance and difficulty in meeting practical application requirements.
The composite film was prepared by acidification treatment, reaction and sintering.
It has achieved a multi-stage pore structure, large specific surface area, good flexibility and self-supporting electrode material, with extremely high specific capacitance and good charge and discharge cycle performance.
Smart Images

Figure CN116553613B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and in particular to a hafnium tantalum oxide-single-walled carbon nanotube composite film and a preparation method and application thereof. Background Art
[0002] As all kinds of electronic products develop towards miniaturization, lightness and wearability, the development of small and lightweight flexible energy storage devices has become a rigid demand of the future electronics industry. Supercapacitors have the advantages of high power density, fast charging and discharging speed, wide operating temperature range and long service life. They stand out among many energy storage devices and have broad application prospects. At present, supercapacitor electrode materials can be divided into double-layer capacitor electrode materials (for example: carbon nanotubes (CNT), graphene (GO), conductive polymers, etc.) and pseudocapacitor electrode materials (for example: MnO2, Co3O4, MOF, etc.). Each has its own advantages and disadvantages. The former has the advantages of light weight, good flexibility and high conductivity, but the specific capacitance is relatively limited, while the latter has the advantages of high specific capacitance, rich material variety and fast charging and discharging rate, but poor conductivity. In summary, the existing supercapacitor electrode materials have obvious defects and it is difficult to fully meet the requirements of practical applications.
[0003] Therefore, it is of great significance to develop an electrode material with better comprehensive performance. Summary of the invention
[0004] The object of the present invention is to provide a hafnium tantalum oxide-single-walled carbon nanotube composite film and a preparation method and application thereof.
[0005] The technical solution adopted by the present invention is:
[0006] A method for preparing a hafnium tantalum oxide-single-walled carbon nanotube composite film comprises the following steps:
[0007] 1) adding single-walled carbon nanotubes into a sulfuric acid-nitric acid mixed solution for acidification to obtain acidified single-walled carbon nanotubes;
[0008] 2) adding the acidified single-walled carbon nanotubes, hafnium source, tantalum source and catalyst into an organic solvent for reaction, and then filtering to form a membrane,
[0009] The film is then placed in a protective atmosphere for sintering to obtain a hafnium tantalum oxide-single-walled carbon nanotube composite film.
[0010] Preferably, the sulfuric acid-nitric acid mixed solution in step 1) is prepared by mixing a sulfuric acid solution with a mass fraction of 50% to 98% and a nitric acid solution with a mass fraction of 30% to 68% in a volume ratio of 1:0.3 to 3.
[0011] Preferably, the acidification treatment in step 1) is carried out at 50°C to 150°C, and the acidification treatment time is 0.5h to 8h.
[0012] Preferably, in step 2), the ratio of the total mass of the hafnium element and the tantalum element in the hafnium source and the tantalum source to the mass of the acidified single-walled carbon nanotubes is 20 to 100:1.
[0013] Preferably, in step 2), the molar ratio of the hafnium element in the hafnium source to the tantalum element in the tantalum source is 3:1.
[0014] Preferably, the hafnium source in step 2) is at least one of hafnium isopropoxide, hafnium n-butoxide, hafnium acetylacetonate, hafniumocene dichloride, hafnium tetrachloride, and pentamethylcyclopentadienyl hafnium trichloride.
[0015] Preferably, the tantalum source in step 2) is at least one of tantalum isopropoxide, tantalum n-butoxide, tantalum acetylacetonate, tantalum trichloride, tantalum pentachloride, and tantalum penta(diethylamine).
[0016] Preferably, the catalyst in step 2) is an aqueous solution of n-propanol.
[0017] Preferably, the mass fraction of the n-propanol aqueous solution is 50% to 75%.
[0018] Preferably, the molar ratio of the hafnium element in the hafnium source to the water in the n-propanol aqueous solution is 1:0.6-2.
[0019] Preferably, the organic solvent in step 2) is at least one of acetylacetone, methyl tert-butyl ether, 1,2-diethoxyethane, ethylene glycol methyl ether, and tetrahydrofuran.
[0020] Preferably, the reaction in step 2) is carried out at 60°C to 150°C, and the reaction time is 0.5h to 24h.
[0021] Preferably, the sintering in step 2) is carried out at 400° C. to 1000° C., and the sintering time is 0.5 h to 48 h.
[0022] A hafnium tantalum oxide-single-wall carbon nanotube composite film is made by the above preparation method.
[0023] Preferably, the thickness of the hafnium tantalum oxide-single-walled carbon nanotube composite film is 50 μm to 100 μm.
[0024] An electrode material comprises the above-mentioned hafnium tantalum oxide-single-walled carbon nanotube composite film.
[0025] A supercapacitor comprises the electrode material.
[0026] The beneficial effects of the present invention are as follows: the hafnium tantalum oxide-single-walled carbon nanotube composite film of the present invention has a multi-level pore structure, a large specific surface area, good flexibility and self-support, an extremely high specific capacitance, and good charge-discharge cycle performance, and its preparation method is simple, efficient and economical, and has broad application prospects in the fields of sustainable energy and electrochemical energy storage.
[0027] Specifically:
[0028] 1) The hafnium tantalum oxide-single-walled carbon nanotube composite film of the present invention solves the problem that transition metal oxide (TMO) materials are difficult to adhere to the surface of carbon materials for a long time, thereby improving the cycle stability of the material and extending its service life;
[0029] 2) The TMO material in the hafnium tantalum oxide-single-walled carbon nanotube composite film of the present invention can be prepared at a relatively low temperature, which can effectively prevent the structural collapse of the carbon material at high temperatures;
[0030] 3) The hafnium tantalum oxide-single-walled carbon nanotube composite film of the present invention enhances the charge transfer capability between the TMO material and the carbon material, and has excellent electrochemical energy storage performance, which is much higher than that of similar TMO / C materials;
[0031] 4) The preparation method of the hafnium tantalum oxide-single-walled carbon nanotube composite film of the present invention is simple, efficient and economical. The solvent used in the preparation process is easy to recover and reuse, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a physical picture of HTO@aCNT in Example 1.
[0033] Figure 2 This is an optical microscope image of the cross section of HTO@aCNT in Example 1.
[0034] Figure 3 This is the XRD pattern of HTO@aCNT in Example 1.
[0035] Figure 4 This is the SEM image of HTO@aCNT in Example 2.
[0036] Figure 5 This is the TEM image of HTO@aCNT in Example 2.
[0037] Figure 6 This is the CV curve of HTO@aCNT in Example 3.
[0038] Figure 7 This is the GCD curve of HTO@aCNT in Example 3.
[0039] Figure 8This is a graph showing the specific capacitance test results of HTO@aCNT in Example 4 at different current densities.
[0040] Fig. 9 This is a graph showing the comparative test results of the specific capacitance of HTO@aCNT in Example 4 and similar materials. DETAILED DESCRIPTION
[0041] The present invention will be further explained and illustrated below in conjunction with specific embodiments.
[0042] Embodiment 1:
[0043] A hafnium tantalum oxide-single-walled carbon nanotube composite film, the preparation method of which comprises the following steps:
[0044] 1) 1 g of single-walled carbon nanotubes (SWCNT) was added to 50 mL of a sulfuric acid-nitric acid mixed solution (prepared by mixing a 98% sulfuric acid solution and a 68% nitric acid solution in a volume ratio of 1:3), and acidified at 100° C. for 4 h, and then cooled to room temperature after adding ice cubes, filtered, and the filtered solid was washed with ethanol and deionized water for 3 times each (until the filtrate was neutral or weakly acidic), and then placed in a vacuum drying oven for drying to obtain acidified single-walled carbon nanotubes;
[0045] 2) cutting the acidified single-walled carbon nanotubes into pieces and adding them into n-propanol, and then performing ultrasonic dispersion to prepare an acidified single-walled carbon nanotube dispersion;
[0046] 3) dissolving hafnium isopropoxide in 1,2-diethoxyethane, and then dropping acetylacetone, the mass ratio of hafnium isopropoxide, 1,2-diethoxyethane, and acetylacetone being 1:5:2, and then stirring evenly at 50° C. to obtain a hafnium isopropoxide solution;
[0047] 4) dissolving tantalum isopropoxide in 1,2-diethoxyethane, and then dropping acetylacetone, the mass ratio of tantalum isopropoxide, 1,2-diethoxyethane, and acetylacetone being 1:5:2, and then stirring evenly at 50° C. to obtain a tantalum isopropoxide solution;
[0048] 5) The hafnium isopropoxide solution and the tantalum isopropoxide solution are mixed uniformly in a molar ratio of hafnium to tantalum of 3:1, and then added to the acidified single-walled carbon nanotube dispersion, the ratio of the total mass of hafnium and tantalum to the mass of the acidified single-walled carbon nanotube is 50:1, and then the temperature is raised to 100° C. and a 75% by mass aqueous solution of n-propanol is added dropwise, the molar ratio of hafnium to water is 1:2, and then the reaction is carried out at a constant temperature for 2 hours, and then filtered, and the film obtained by filtration is washed with alcohol and ammonia water for 3 times respectively, and then placed in a vacuum drying oven for drying, and then placed in a tubular furnace for sintering at 750° C. in an oxygen-free atmosphere for 2 hours to obtain a hafnium tantalum oxide-single-walled carbon nanotube composite film (denoted as HTO@aCNT).
[0049] Performance Testing:
[0050] 1) The actual image of the hafnium tantalum oxide-single-walled carbon nanotube composite film (HTO@aCNT) in this embodiment is as follows Figure 1 The optical microscope image of the cross section is shown in Figure 2 As shown, the X-ray diffraction (XRD) pattern is as follows Figure 3 shown.
[0051] Depend on Figure 1 It can be seen that the HTO@aCNT in this embodiment has good flexibility and can be curled into shape with any curvature radius.
[0052] Depend on Figure 2 It can be seen that the thickness of HTO@aCNT in this embodiment is 50 μm to 100 μm.
[0053] Depend on Figure 3 It can be seen that the characteristic peaks of HTO crystals and SWCNTs appeared, indicating that the HTO crystals were successfully loaded on SWCNTs.
[0054] 2) HTO@aCNT and polyvinylidene fluoride were dispersed in N-methylpyrrolidone (NMP) and dried at 80°C for 1 h to prepare a working electrode. A platinum sheet was used as a counter electrode, a saturated calomel electrode (SCE) was used as a reference electrode, and a solution of H2SO4, Na2SO4 and KOH with a concentration of 1 mol / L was used as an electrolyte. The CV curve (tested at a scan rate of 10 mV / s to 200 mV / s) and GCD curve (tested at a scan rate of 5 mA / cm2) of HTO@aCNT were obtained by three-electrode method. 2 ~100mA / cm 2 The specific capacitance of HTO@aCNT was 5230.1mF / cm 2 , the voltage window is 2V, and the specific capacitance retention rate is 79.3% after 5000 cycles of discharge.
[0055] Embodiment 2:
[0056] A hafnium tantalum oxide-single-walled carbon nanotube composite film, the preparation method of which comprises the following steps:
[0057] 1) adding 1 g of single-walled carbon nanotubes (SWCNT) to 50 mL of a sulfuric acid-nitric acid mixed solution (prepared by mixing 80% by mass sulfuric acid solution and 50% by mass nitric acid solution in a volume ratio of 1:2), acidifying at 120° C. for 1 h, then adding ice cubes and cooling to room temperature, filtering, and washing the filtered solid with ethanol and deionized water for 3 times each (until the filtrate is neutral or weakly acidic), and then drying in a vacuum drying oven to obtain acidified single-walled carbon nanotubes;
[0058] 2) cutting the acidified single-walled carbon nanotubes into pieces and adding them into n-propanol, and then performing ultrasonic dispersion to prepare an acidified single-walled carbon nanotube dispersion;
[0059] 3) dissolving hafnium n-butoxide in methyl tert-butyl ether, and then dropping acetylacetone, the mass ratio of hafnium n-butoxide, methyl tert-butyl ether, and acetylacetone being 1:10:1, and then stirring evenly at 70° C. to obtain a hafnium n-butoxide solution;
[0060] 4) dissolving tantalum n-butoxide in methyl tert-butyl ether, then dropping acetylacetone, the mass ratio of tantalum n-butoxide, methyl tert-butyl ether and acetylacetone being 1:10:1, and then stirring evenly at 70° C. to obtain a tantalum n-butoxide solution;
[0061] 5) The hafnium n-butoxide solution and the tantalum n-butoxide solution were mixed evenly in a molar ratio of hafnium to tantalum of 3:1, and then added to the acidified single-walled carbon nanotube dispersion, the ratio of the total mass of hafnium and tantalum to the mass of the acidified single-walled carbon nanotubes was 50:1, and then the temperature was raised to 100° C. and a 50% by mass aqueous solution of n-propanol was added dropwise, the molar ratio of hafnium to water was 1:1, and then the reaction was carried out at a constant temperature for 4 hours, and then filtered, and the film obtained by filtration was washed with alcohol and ammonia water for 3 times respectively, and then placed in a vacuum drying oven for drying, and then placed in a tubular furnace for sintering at 850° C. in an oxygen-free atmosphere for 1 hour to obtain a hafnium tantalum oxide-single-walled carbon nanotube composite film (denoted as HTO@aCNT).
[0062] Performance Testing:
[0063] 1) The scanning electron microscope (SEM) image of the hafnium tantalum oxide-single-walled carbon nanotube composite film (HTO@aCNT) in this embodiment is as follows: Figure 4 As shown in the transmission electron microscope (TEM) image Figure 5 (3 magnifications) shown.
[0064] Depend on Figure 4 It can be seen that single-walled carbon nanotubes are aggregated into carbon tube bundles of about 50 nm, and HTO crystals are evenly distributed on the surface of SWCNT.
[0065] Depend on Figure 5 It can be seen that the HTO crystals are tightly adhered to the surface of SWCNTs, and the size of the HTO crystals is about 10 nm.
[0066] 2) Referring to Example 1, the CV curve (tested at a scan rate of 10 mV / s to 200 mV / s) and GCD curve (tested at 5 mA / cm 2 ~100mA / cm 2 The specific capacitance of HTO@aCNT was 4685.1mF / cm 2, the voltage window is 2V, and the specific capacitance retention rate is 79.3% after 5000 cycles of discharge.
[0067] Embodiment 3:
[0068] A hafnium tantalum oxide-single-walled carbon nanotube composite film, the preparation method of which comprises the following steps:
[0069] 1) adding 1 g of single-walled carbon nanotubes (SWCNT) to 50 mL of a sulfuric acid-nitric acid mixed solution (prepared by mixing a 66% sulfuric acid solution and a 34% nitric acid solution in a volume ratio of 1:0.3), acidifying at 90° C. for 4 h, then adding ice cubes and cooling to room temperature, filtering, and washing the filtered solid with ethanol and deionized water for 3 times each (until the filtrate is neutral or weakly acidic), and then drying in a vacuum drying oven to obtain acidified single-walled carbon nanotubes;
[0070] 2) cutting the acidified single-walled carbon nanotubes into pieces and adding them into n-propanol, and then performing ultrasonic dispersion to prepare an acidified single-walled carbon nanotube dispersion;
[0071] 3) dissolving hafnium dichloride in a mixed solution of 1,2-diethoxyethane and ethylene glycol methyl ether, wherein the mass ratio of hafnium dichloride, 1,2-diethoxyethane and ethylene glycol methyl ether is 1:4:4, and stirring evenly at 120° C. to obtain a hafnium dichloride solution;
[0072] 4) dissolving tantalum acetylacetonate in a mixed solution of 1,2-diethoxyethane and ethylene glycol methyl ether, wherein the mass ratio of tantalum acetylacetonate, 1,2-diethoxyethane and ethylene glycol methyl ether is 1:4:4, and stirring evenly at 120° C. to obtain a tantalum acetylacetonate solution;
[0073] 5) The hafnium dichloride solution and the tantalum acetylacetonate solution were mixed uniformly in a molar ratio of hafnium to tantalum of 3:1, and then added to the acidified single-walled carbon nanotube dispersion, the ratio of the total mass of hafnium and tantalum to the mass of the acidified single-walled carbon nanotubes was 50:1, and then the temperature was raised to 100° C. and a 50% by mass aqueous solution of n-propanol was added dropwise, the molar ratio of hafnium to water was 1:0.6, and then the mixture was reacted at a constant temperature for 12 hours, and then filtered, and the film obtained by filtration was washed with alcohol and ammonia water for 3 times respectively, and then placed in a vacuum drying oven for drying, and then placed in a tubular furnace for sintering at 650° C. in an oxygen-free atmosphere for 6 hours to obtain a hafnium tantalum oxide-single-walled carbon nanotube composite film (denoted as HTO@aCNT).
[0074] Performance Testing:
[0075] Referring to Example 1, the CV curve of HTO@aCNT was obtained by three-electrode method (tested at a scan rate of 10 mV / s to 200 mV / s). Figure 6As shown, the GCD curve (at 5 mA / cm 2 ~100mA / cm 2 Tested at a current density of Figure 7 shown.
[0076] Depend on Figure 6 and Figure 7 It can be seen that the specific capacitance of HTO@aCNT is 5583.4mF / cm 2 , the voltage window is 2V, and the specific capacitance retention rate is 76.2% after 5000 cycles of discharge.
[0077] Embodiment 4:
[0078] A hafnium tantalum oxide-single-walled carbon nanotube composite film, the preparation method of which comprises the following steps:
[0079] 1) adding 1 g of single-walled carbon nanotubes (SWCNT) to 50 mL of a sulfuric acid-nitric acid mixed solution (prepared by mixing a sulfuric acid solution of 98% by mass and a nitric acid solution of 34% by mass in a volume ratio of 1:0.3), acidifying at 90° C. for 2 h, then adding ice cubes and cooling to room temperature, filtering, and washing the filtered solid with ethanol and deionized water for 3 times each (until the filtrate is neutral or weakly acidic), and then drying in a vacuum drying oven to obtain acidified single-walled carbon nanotubes;
[0080] 2) cutting the acidified single-walled carbon nanotubes into pieces and adding them into n-propanol, and then performing ultrasonic dispersion to prepare an acidified single-walled carbon nanotube dispersion;
[0081] 3) dissolving hafnium dichloride in ethylene glycol methyl ether, and then dropping acetylacetone, the mass ratio of hafnium dichloride, ethylene glycol methyl ether, and acetylacetone being 1:10:1, and then stirring evenly at 80° C. to obtain a hafnium dichloride solution;
[0082] 4) dissolving tantalum isopropoxide in ethylene glycol methyl ether, then dropping acetylacetone, the mass ratio of tantalum isopropoxide, ethylene glycol methyl ether and acetylacetone being 1:10:1, and then stirring evenly at 80° C. to obtain a tantalum isopropoxide solution;
[0083] 5) The hafnium dichloride solution and the tantalum isopropoxide solution were mixed evenly in a molar ratio of hafnium to tantalum of 3:1, and then added to the acidified single-walled carbon nanotube dispersion, the ratio of the total mass of hafnium and tantalum to the mass of the acidified single-walled carbon nanotubes was 50:1, and then the temperature was raised to 110° C. and a 70% by mass aqueous solution of n-propanol was added dropwise, the molar ratio of hafnium to water was 1:1, and then the reaction was carried out at a constant temperature for 16 hours, and then filtered, and the film obtained by filtration was washed with alcohol and ammonia water for 3 times respectively, and then placed in a vacuum drying oven for drying, and then placed in a tubular furnace for sintering at 950° C. in an oxygen-free atmosphere for 0.5 h to obtain a hafnium tantalum oxide-single-walled carbon nanotube composite film (denoted as HTO@aCNT).
[0084] Performance Testing:
[0085] 1) Referring to Example 1, the CV curve (tested at a scan rate of 10 mV / s to 200 mV / s) and GCD curve (tested at 5 mA / cm 2 ~100mA / cm 2 The specific capacitance of HTO@aCNT was 5862.5mF / cm 2 , the voltage window is 2V, and the specific capacitance retention rate is 82.1% after 5000 cycles of discharge.
[0086] 2) The specific capacitance test results of HTO@aCNT in this embodiment at different current densities are shown in the figure below: Figure 8 shown.
[0087] Depend on Figure 8 It can be seen that with the increase of current density, the specific capacitance of HTO@aCNT decreases. 2 The specific capacitance retention rate is still 74.5% at high current density, showing good rate performance.
[0088] 3) The comparative test results of the specific capacitance of HTO@aCNT in this embodiment and similar materials (GCP@PPy, CNT / PANI, CNF / CNT / RGO, VACNTs, CNT / PC, P3MT / HACNT / / HACNT and MnO2 / CNTs) are shown in the figure below: Fig. 9 And as shown in Table 1.
[0089] Table 1 Comparative test results of specific capacitance of HTO@aCNT and similar materials
[0090]
[0091]
[0092] Depend on Fig. 9 As shown in Table 1, the HTO@aCNT of the present invention has obvious energy storage advantages compared with similar flexible transition metal oxide-carbon material composite films, and is an electrochemical energy storage material with great potential.
[0093] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a hafnium tantalum oxide-single-walled carbon nanotube composite film, characterized in that: The following steps are involved: 1) adding single-walled carbon nanotubes into a sulfuric acid-nitric acid mixed solution for acidification to obtain acidified single-walled carbon nanotubes; 2) adding the acidified single-walled carbon nanotubes, hafnium source, tantalum source and catalyst into an organic solvent for reaction, filtering to form a film, and then sintering in a protective atmosphere to obtain a hafnium tantalum oxide-single-walled carbon nanotube composite film; Step 2) the hafnium source is at least one of hafnium isopropoxide, hafnium n-butoxide, hafnium acetylacetonate, hafnium cyclopentadienyl dichloride, hafnium tetrachloride, and pentamethylcyclopentadienyl hafnium trichloride; Step 2) the tantalum source is at least one of tantalum isopropoxide, tantalum n-butoxide, tantalum acetylacetonate, tantalum trichloride, tantalum pentachloride, and tantalum penta(diethylammonium); Step 2) the catalyst is an aqueous solution of n-propanol; Step 2) The reaction is carried out at 60°C to 150°C, and the reaction time is 0.5h to 24h.
2. The preparation method according to claim 1, characterized in that: Step 1) The sulfuric acid-nitric acid mixed solution is prepared by mixing a sulfuric acid solution having a mass fraction of 50% to 98% and a nitric acid solution having a mass fraction of 30% to 68% in a volume ratio of 1:0.3 to 3.
3. The preparation method according to claim 1 or 2, characterized in that: Step 1) The acidification treatment is carried out at 50°C to 150°C, and the acidification treatment time is 0.5h to 8h.
4. The preparation method according to claim 1, characterized in that: Step 2) The ratio of the total mass of the hafnium element and the tantalum element in the hafnium source and the tantalum source to the mass of the acidified single-walled carbon nanotubes is 20-100:1; Step 2) The molar ratio of the hafnium element in the hafnium source to the tantalum element in the tantalum source is 3:
1.
5. The preparation method according to claim 1 or 4, characterized in that: Step 2) The organic solvent is at least one of acetylacetone, methyl tert-butyl ether, 1,2-diethoxyethane, ethylene glycol methyl ether, and tetrahydrofuran.
6. The preparation method according to claim 1 or 4, characterized in that: Step 2) The sintering is carried out at 400°C to 1000°C, and the sintering time is 0.5h to 48h.
7. A hafnium tantalum oxide-single-walled carbon nanotube composite film, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.
8. An electrode material, characterized in that A hafnium tantalum oxide-single-walled carbon nanotube composite film comprising the hafnium tantalum oxide-single-walled carbon nanotube composite film as claimed in claim 7.
9. A supercapacitor, characterized in that: Contains the electrode material according to claim 8.